Antibodies to neutrophil elastase: a study in patients with vasculitis - Beyer, Susanne; Andrassy, Konrad; Wörner, Inga; Hänsch, Gertrud Maria; Roland, J.; Morcos, Michael; Ritz, Eberhard (American journal of kidney diseases, 1996)
Whether antibodies to elastase (EL) exist in autoimmune disease is controversial, due in part to inadequate methods used to determine antibody titers. We have developed a highly sensitive and specific enzyme-linked immunosorbent assay, using immobilized EL and mouse monoclonal antibodies for standardization. The specificity of the enzyme-linked immunosorbent assay was confirmed by absorption studies and Western blot analysis. Using this enzyme-linked immunosorbent assay, antibodies to EL were found in antineutrophil cytoplasmic antibody-positive vasculitis patients to a higher degree than reported in the literature (in eight of 108 patients with Wegener's granulomatosis and in 15 of 78 patients with microscopic polyangiitis). Patients with Wegener's granulomatosis or microscopic polyangiitis and antibodies to EL had significantly more severe renal involvement, as indicated by the higher frequency of dialysis dependency. Also in contrast to reported data, antibodies to EL were found less frequently in patients with systemic lupus erythematosus (nine of 64 patients). Binding of systemic lupus erythematosus sera to uncoated plates, giving a nonspecific reaction, was seen quite frequently, which might explain the discrepancy.